Creating Beginner Student-Preneurs Through Human Resource Investment - Fahmi, Zul; Jam'an , Andi; Harrang, Agus Salim (Manunggal Halim Jaya, 2024)
The independent entrepreneurship program is a program initiated by the Ministry of Education, Culture, Research, and Technology aimed at students who have an interest in the world of business, and provides students with the opportunity to be part of this independent entrepreneurship program. Independent Learning Campus Policy (MBKM). Muhammadiyah University of Makassar as one of the implementing campuses has collaborated in the last few years in implementing this independent entrepreneurship program. This can be seen as an important effort to invest in more specific human capital that will prepare and encourage students to enter the world of economics, especially entrepreneurship. The type of research used in this research is a qualitative approach. The collection technique uses tri-angulation, data analysis is inductive and qualitative, and the results of qualitative research emphasize meaning rather than generalization (Sugiyoni, 2011). The unit of analysis in this research is the individual as an informant. The informants in this research are employees, some of whom have certain positions to fulfill several informant criteria in this research, namely informants who have been working for a long time, informants who are willing to provide information regarding the research object, informants who are directly involved in all activities of the independent entrepreneurship program. The data analysis technique for this research uses a qualitative descriptive method, namely presenting data in written form and explaining what it is according to the data obtained from the research results. The results of this research invite students to be more practical through the process of providing entrepreneurial mindsets and competencies, developing and creating business concepts, entrepreneurial practices and development. Opportunity to study outside campus to develop knowledge in the field of entrepreneurship. This program will also provide benefits for students to get credit recognition from a series of activities carried out amounting to the equivalent of 20 credits.